The Arabidopsis R2R3 MYB Transcription Factor MYB15 Is a Key Regulator of Lignin Biosynthesis in Effector-Triggered Immunity - Kim, Seu Ha; Lam, Pui Ying; Lee, Myoung-Hoon; Jeon, Hwi Seong; Tobimatsu, Yuki; Park, Ohkmae K. (Frontiers in Plant Science, 2020)
Lignin, a major component of the secondary cell wall, is important for plant growth and development. Moreover, lignin plays a pivotal role in plant innate immunity. Lignin is readily deposited upon pathogen infection and functions as a physical barrier that limits the spread of pathogens. In this study, we show that an Arabidopsis MYB transcription factor MYB15 is required for the activation of lignin biosynthesis genes such as PAL, C4H, 4CL, HCT, C3′H, COMT, and CAD, and consequently lignin formation during effector-triggered immune responses. Upon challenge with the avirulent bacterial pathogen Pst DC3000 (AvrRpm1), lignin deposition and disease resistance were reduced in myb15 mutant plants. Furthermore, whereas invading pathogens, together with hypersensitive cell death, were restricted to the infection site in wild-type leaves, they spread beyond the infected area in myb15 mutants. The exogenous supply of the lignin monomer coniferyl alcohol restored lignin production and rescued immune defects in myb15 plants. These results demonstrate that regulation at the transcriptional level is key to pathogen-induced lignification and that MYB15 plays a central role in this process.